2019
DOI: 10.1055/s-0039-1692672
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcome and Conservative Treatment Failure in Patients with Skull Fracture after Traumatic Brain Injury: A Retrospective Cohort Study

Abstract: Objective Traumatic brain injury (TBI) remains a major cause of morbidity and mortality worldwide. The prognostic value of skull fracture (SF) remains to be clearly defined. To evaluate the need for neurosurgical intervention and determine the risk factors of conservative treatment failure (CTF), we retrieved from the hospital database the records of patients with SF after TBI. Methods We analyzed 146 consecutive patients (mean age: 49.8 ± 17.5 years) treated at the department of neurosurgery in a 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The skull fracture among TBI patients is associated with an increased risk of neurosurgically-relevant intracranial lesion [64]. Bobeff et al showed a higher incidence of complications during treatment in patients with linear skull fracture [41]. Our results did not include fractures as factors of unfavorable prognosis.…”
Section: Computer Tomography Scan Characteristicsmentioning
confidence: 49%
See 2 more Smart Citations
“…The skull fracture among TBI patients is associated with an increased risk of neurosurgically-relevant intracranial lesion [64]. Bobeff et al showed a higher incidence of complications during treatment in patients with linear skull fracture [41]. Our results did not include fractures as factors of unfavorable prognosis.…”
Section: Computer Tomography Scan Characteristicsmentioning
confidence: 49%
“…High glucose is a cause of secondary insults for the patients after TBI, and it is associated with a poorer outcome [40]. This trend was also noted in observations carried out by Bobeff et al The authors showed that patients with glucose levels exceeding 160 mg/dL are at a higher risk of complications after treatment [41]. Similarly, the work of Corbett et al [42] showed that disorders in this area are associated with higher risk of unfavorable outcome at 18 months after severe TBI.…”
Section: Laboratory Variablesmentioning
confidence: 73%
See 1 more Smart Citation
“…Common entry points include the sphenoidal roof, lamina cribrosa, petrous bone, middle ear, and Eustachian tube, facilitating CSF's access into the nasal cavity. However, determining the leak's lateral origin based on the nostril side is often unreliable, with nasal cavity fractures due to traumatic CSF leaks comprising 3-4% of cases (4)(5)(6). Typically, acute traumatic CSF leaks first present with bloody cerebrospinal fluid, which eventually clears.…”
Section: Introductionmentioning
confidence: 99%